Analytical Network Process (ANP) for priority setting of strategic roads handling at Tebo Regency. (August 2019) - Yosritzal,; Permana, J; Istijono, B; Hidayat, B; Ophiyandri, T; Gunawan, H
Abstract: Development of transportation infrastructure in the region aims to meet the needs of the community to facilitate mobility of people, goods, and services. However, the work of transportation infrastructure requires a large amount of cost while the development budget is limited. Therefore, a careful determination of the priority of road handling is urgently required. In this study, an analysis was conducted to determine the priority of handling strategic roads in Tebo Regency. This study uses the Analytic Network Process (ANP) method with 4 (four) criteria to determine the priority of road handling, namely: engineering, economics, regional potential, and policies. It was found that National Road - Pintas being the first priority with a weight of 0.252, then the second priority for National Road - Lubuk Mandarsah with a weight of 0.23.The third priority is Unit I Rimbo Bujang - Unit XI Rimbo Ulu Road with a weight of 0.211.